?Reduction In Post-Harvest Losses of Winter and Summer Crops of Guava: Short Communications - WAHEED, A; SHAH, W, .H.; SHAH, F H. (Biological Sciences - PJSIR, 1995)
Guava (Psidium guajava) is a perishable commodity and has a very short shelf-life at ambient temperature. Extension in shelf-life of fruits by reducing enzymic activity,